Making a Difference: Canadian Women Writers and the Fiction of Social Justice - Gerson, Carole (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada, 2023)
In January 1944, when the influential Toronto critic William Arthur Deacon lamented the absence of a Canadian “equivalent of ‘Uncle Tom’s Cabin’” because Canadians are “still pioneering, still afraid of ourselves intellectually and emotionally,”[1] little did he know that a significant candidate was on the horizon. Gwethalyn Graham’s second novel, Earth and High Heaven, which appeared later that year, launched an analysis of anti-Semitism that was quickly embraced by cultural arbiters and the general public in both Canada and the United States. This essay situates the production and reception history of Graham’s book in relation to other novels by English-Canadian women writers that advocated for social change, and offers cases studies of the three most widely disseminated works that used the power of fiction to marshal empathy: Marshall Saunders’s Beautiful Joe (1894), Graham’s Earth and High Heaven (1944) and Joy Kogawa’s Obasan (1981).